Modeling Electroabsorption Modulated Laser for Digital Optical Transmission - Belkin, M.E.; Golovin, V.; Sigov, A.S.; Tyschuk, Y. (2018 IEEE British and Irish Conference on Optics and Photonics (BICOP), 2018)
We propose and discuss a new equivalent circuit model to computer-aided design a high-speed electroabsorption modulated laser for the upcoming wireless telecom systems using well-known microwave-electronic software tool NI AWRDE. To validate the model some simulation experiments were conducted including light-current, emitted wavelength, and large-signal intermodulation distortion, were studied. As an outcome of the conducted simulation experiments, the key parameters and characteristics correspond to the real product analogues. Another simulation experiment was referred to fiber-optics transmission of 10 Gbaud per second 16QAM digital signal on the RF carrier of 25 GHz over the single-mode optical fiber of the different length. In the result, the simulated values of error vector magnitudes were less than 1% in back-to-back configuration and met standard requirements for passive optical networks at practical output signal-to-noise ratio of 50 dB in the fiber length range up to 10 km.